Relative Salinity Tolerance of Pearl Millet Hybrids and Populations - Dua, R P; Bhattacharyya, R K (Annals of Arid Zone, 2016)
Relative salinity tolerance of hybrids vs populations in pearl millet was assessed for a set of 48 genotypes grown in normal and saline soils, by scoring of the per cent reduction in yield attributes on a 1-5 scale. Populations were relatively better tolerant than hybrids for grain yield. Tall populations with long ears are better suited in saline soils. Plant height and ear length were highly correlated with grain yield. Hybrids gave higher absolute yield than populations in saline soils, indicating a scope of developing salt tolerant hybrids from inbreds of salinity tolerant populations. Bold seeded and bristled hybrids have high salinity tolerance.